Evaluation of Fe uptake and translocation in transgenic and non-transgenic soybean plants using enriched stable Fe-57 as a tracer - Oliveira, Silvana R.; Menegario, Amauri A. [UNESP]; Arruda, Marco A. Z. (Royal Soc Chemistry, 2014)
A tracer experiment is carried out with transgenic T (variety M 7211 RR) and non-transgenic NT (variety MSOY 8200) soybean plants to evaluate if genetic modification can influence the uptake and translocation of Fe. A chelate of EDTA with enriched stable Fe-57 is applied to the plants cultivated in vermiculite plus substrate and the Fe-57 acts as a tracer. The exposure of plants to enriched Fe-57 causes the dilution of the natural previously existing Fe in the plant compartments and then the changed Fe isotopic ratio (Fe-57/Fe-56) is measured using a quadrupole-based inductively coupled plasma mass spectrometer equipped with a dynamic reaction cell (DRC). Mathematical calculations based on the isotope dilution methodology allow distinguishing the natural abundance Fe from the enriched Fe (incorporated during the experiment). The NT soybean plants acquire higher amounts of Fe from natural abundance (originally present in the soil) and from enriched Fe (coming from the Fe-57-EDTA during the experiment) than T soybean ones, demonstrating that the NT soybean plants probably absorb higher amounts of Fe, independently of the source. The percentage of newly incorporated Fe (coming from the treatment) was approximately 2.0 and 1.1% for NT and T soybean plants, respectively. A higher fraction (90.1%) of enriched Fe is translocated to upper parts, and a slightly lower fraction (3.8%) is accumulated in the stems by NT plants than by T ones (85.1%; 5.1%). Moreover, in both plants, the Fe-EDTA facilitates the transport and translocation of Fe to the leaves. The genetic modification is probably responsible for differences observed between T and NT soybean plants.